Media work, career management, and professional identity: Living labour precarity - Elefante, Phoebe Harris and Deuze, Mark (Northern Lights: Film & Media Studies Yearbook, 2012)
Understanding creative industries in general and media work in particular poses a fascinating paradox: as people worldwide engage with media in an increasingly immersive, always-on, almost instantaneous and interconnected way, the very people whose livelihoods and sense of professional identity depend on delivering content and experiences across such media seem to be at a loss on how to come up with survival strategies – in terms of business models, effective regulatory practices (e.g. copyrights and universal access provisions), and perhaps most significantly the organization of entrepreneurial working conditions that support and sustain the creative process needed to meet the demands of a global market saturated with media. This article proposes a model for professional identity in media work that engages with these questions, based on past, present and ongoing personal experiences of one of the authors as a self-employed media worker in multiple creative industries.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTM4Ni9ubC4xMC4xLjlfMQ